PENGARUH GELOMBANG MIKRO (MICROWAVE ASSISTED) TERHADAP KURVA HISTERISIS DARI BAHAN FERROMAGNETIK CoPd BERBENTUK ELLIPSOID - Widia Nursiyanto; L Rohman; H.T.B.F Nagara; E Supriyanto (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
Abstract Until now the data storage device is still constrained unstable because of the super paramagnetic effect. This effect can occur when the value of bit density increases or when the magnetic energy decreases which causes the process of demagnetization due to the magnetization orientation changed in the presence of high temperature. CoPd as one of the ferromagnetic materials has magnetic anisotropy value and large coercivity of the field, so that this material can be patterned with very small size according to the requirement of data storage tool. However, data analysis of the CoPd hysteresis curve is required when the microwave assisted at the CoPd would give to rise of temperature. Therefore, we observe the value of the coercivity of the field on the ellipsoid CoPd material with the dimension of size the diameter varied. In addition external field, the microwave assisted with the value of amplitude is 10000 mT and the value of frequency is 80 GHz give to the sample. Retrieval of data using a micromagnetic simulation program from a public software called Object Oriented Micromagnetic Framework (OOMMF). From the data processing, it is found that coercivity of the field becomes smaller when dimension of sample are getting bigger, This means that the reversal of magnetization of CoPd is getting smaller. With these results it can be concluded that CoPd are suitable for use as data storage devices. The best dimensions are (150x150x450) nm3 and (165x165x495) nm3. Keywords: CoPd, hysteresis curve, microvawe assisted, coercivity of the field